Environmental Education Model to the conservation of the natural resources: a proposal to the Poas Volcano National Park, Costa Rica (Biocenosis, 2012)
The model proposes the approach of environmental education that is needed to address environmental problems that affect natural resources. Its construction is based on the results of research conducted through case study method and the objectives, principles and objectives of Environmental Education, presented as a process (awareness, knowledge, attitudes, skills, capacity assessment and participation). It is conceived as a system that integrates elements of affective,cognitive and behavioral variables on three levels: awareness, ownership and empowerment, so that as a process, to facilitate the change required to move from awareness to environmental action. From this perspective, the model offers the possibility of working with one, two or three variables, depending on the nature and objectives of educational activities to be performed and the interests and needs of the target group. And aims to facilitate knowledge and skills inthe target groups to develop solutions that minimize the local impact and promote environmentally responsible behavior towards the conservation of natural resources of the Poas Volcano National Park and surrounding areas.
Keywords: Environmental Education as a process; Awareness; Ownership; Empowerment; Environmental responsible behavior